Scale and scope : the dynamics of industrial capitalism - Chandler, Alfred D. (Alfred Dupont), 1918-2007 (Belknap Press, 1994)
Scale and Scope is Alfred Chandler’s first major work since his Pulitzer Prize–winning The Visible Hand. Representing ten years of research into the history of the managerial business system, this book concentrates on patterns of growth and competitiveness in the United States, Germany, and Great Britain, tracing the evolution of large firms into multinational giants and orienting the late twentieth century’s most important developments.